REPRESENTASI PESANTREN DAN KESALAHAN BERBAHASA DALAM NOVEL “CIUMAN TERAKHIR AYAH” KARYA: MAUFIQURRAHMAN SURAHMAN - Kadarisman Kadarisman (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2020)
The novel is one type of prose literary work in which there are building elements such as plot, character, setting, and of course language. As part of literature, novels also have their own genre. Indonesian literature continues to evolve in accordance with the demands and development of the times, and in accordance with the situation and conditions in the community of writers and readers. In the novel Ciuman Terakhir, the work of Maufiqurrahman Surahman will be found in a portrait of the world of pesantren which is very thick. This indicates that the sociology of the author is very influential in constructing a literary work. This can be seen in the way the author chooses diction, plot, builds character, and creates a certain atmosphere in the novel. On the other hand, there are still some language errors in the novel The Last Kiss of the Father. Therefore understanding of linguistic rules is very important, because literary works use language as a medium of liaison between authors and readers.